2008
DOI: 10.1080/01674820801990577
|View full text |Cite|
|
Sign up to set email alerts
|

Maternity blues as predictor of postpartum depression: A prospective cohort study among Japanese women

Abstract: These findings suggest that maternity blues is a strong predictor of postpartum depression. The higher the blues score, the higher the risk of postpartum depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 32 publications
4
24
0
3
Order By: Relevance
“…This outcome was consistent with prior studies [17,18,[30][31][32][33][34]. However, compared with previous studies, we observed different sequences over time regarding mood state, which might indicate a different etiology of depression during pregnancy and postpartum depression.…”
Section: Discussionsupporting
confidence: 89%
“…This outcome was consistent with prior studies [17,18,[30][31][32][33][34]. However, compared with previous studies, we observed different sequences over time regarding mood state, which might indicate a different etiology of depression during pregnancy and postpartum depression.…”
Section: Discussionsupporting
confidence: 89%
“…In met-ropolitan areas, the EPDS positive rate is approximately 13% (Nishizono-Maher et al, 2004;Watanabe et al, 2008); however, in a different medium-sized city from that sampled in this study, the EPDS positive rate at 4 months postpartum was 6.7% (Tamaki et al, 1997). Our findings are in accord with the results reported by Tamaki et al (1997).…”
Section: Epds Scoressupporting
confidence: 59%
“…who found a similar association between GHQ scores during late pregnancy and PPD at the fourth month post‐partum . Other studies also showed that women with PPD were most likely to have psychological symptoms during pregnancy . Three meta‐analyses and additional studies regarding risk factors for PPD on 24 000 subjects concluded that having depression and anxiety during pregnancy and previous history of psychiatric illness are strong risk factors for developing PPD …”
Section: Discussionmentioning
confidence: 82%
“…41 Other studies also showed that women with PPD were most likely to have psychological symptoms during pregnancy. 42,43 Three meta-analyses and additional studies regarding risk factors for PPD on 24 000 subjects concluded that having depression and anxiety during pregnancy and previous history of psychiatric illness are strong risk factors for developing PPD. 11 This study also found that a lack of postnatal parental competence and low parenting self-efficacy were significant risk factors for PPD.…”
Section: Discussionmentioning
confidence: 99%